Anthropometric profile of children attending anganwadi centers under integrated child development services scheme - Panda, Prateek Kumar; Panda, Kalpana; Panda, Pramod Kumar; Nagaraj, Niranjan (International Journal Of Community Medicine And Public Health, 2018)
Background: The first six years of a child’s life are most crucial as the foundations for cognitive, social, emotional, physical, motor and psychological development are laid at this stage. The present study was conducted to assess the nutritional status of children availing the services under Integrated Child Development Service Scheme. Methods: The study was done with house to house survey with the help of a prepared scheduled proforma by personal interview and taking necessary anthropometric measurements and clinical examination. In the present study the following age independent criteria’s are taken into account for the assessment of the nutritional status of the (3-5 years) age group of children in both the I.C.D.S and non I.C.D.S area separately: Mid upper arm circumference; Kanwati’s index; Rao’s index; Bangle screening method. Results: The association of nutritional status and MUAC measurement is statistically significant (p<0.05). The association of nutritional status and Kanawati ratios is statistically significant (p<0.05). The association of the nutritional status and Rao’s index is statistically significant (p<0.05). The number of children in I.C.D.S area with passing of the bangle above the elbow are only 28 and in non – I.C.D.S area, it is 42. In I.C.D.S area the immunisation status is better. Conclusions: I.C.D.S scheme is encouraging and there is no doubt regarding the positive achievements and prospective of I.C.D.S. Still there is much to be done to improve its performance by giving much emphasis on the supplementary nutrition, to the beneficiaries.